Traveller's Palm, Trinidad - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
This postcard shows the Traveller's Palm which has a distinctive fan shape and was given its name because the sheaths of the stem hold drinking water which can be used as an emergency drinking supply. This used postcard,postmarked, 1908, is addressed to Miss K. Ritz of New York,United States of America and affixed is a one cent United States postage stamp.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Traveller's Palm; Ravenala madagascariensis; 1908